2016
DOI: 10.1021/acssuschemeng.5b01740
|View full text |Cite
|
Sign up to set email alerts
|

Nonedible Starch Based “Green” Thermoset Resin Obtained via Esterification Using a Green Catalyst

Abstract: In this study, a biobased thermoset resin was developed from a nonedible starch source obtained from mango processing industrial waste. Mango seed starch (MSS) was extracted from defatted mango seed kernels and cross-linked using a “green” cross-linker/catalyst system, 1,2,3,4-butane tetracarboxylic acid (BTCA)/sodium propionate (NaP), to obtain the thermoset resin. The tensile properties of the cross-linked MSS were found to be adequate to replace edible starch based thermoset resins, e.g., potato or corn or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…A similar effect was observed by N.V. Patil and A.N. Netravali [ 50 ], who esterified mango seed starch extracted from defatted mango seed kernels using 1,2,3,4-butane-tetracarboxylic acid. Moreover, crosslinking by BTCA significantly reduced the percentage of degradation or the weight loss of the samples.…”
Section: Resultssupporting
confidence: 80%
“…A similar effect was observed by N.V. Patil and A.N. Netravali [ 50 ], who esterified mango seed starch extracted from defatted mango seed kernels using 1,2,3,4-butane-tetracarboxylic acid. Moreover, crosslinking by BTCA significantly reduced the percentage of degradation or the weight loss of the samples.…”
Section: Resultssupporting
confidence: 80%
“…Based on the understanding derived from Figure , it can be concluded that MSS was completely gelatinized at 85 °C. Further, the gelatinization temperature of MSS was confirmed using Advance Rheometer‐2000 (TA Instruments, New Castle, DE) equipped with standard steel parallel plate and found to be 80 °C …”
Section: Resultsmentioning
confidence: 99%
“…This confirmed the esterification reaction between the carboxyl groups from BTCA and the hydroxyl groups from MSS which takes place during the curing (hot‐pressing). The BTCA crosslinks with MSS via anhydride formation (Scheme ) in the presence of the catalyst (NaP) which, in turn, reacts with the hydroxyl groups abundantly present and easily available due to gelatinization of MSS . BTCA and NaP have been used to crosslink cellulose earlier .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A major concern about utilizing these sources for technical applications is that they are extracted from edible sources. Considering the increased demand for edible proteins and starches in the future, from human and livestock sectors, it is critical to explore the nonedible sources for technical applications, which will not compete with the edible ones in the food security interest . Some agro‐seeds such as Pongamia pinnata (karanja), Azadirachta indica (neem), and Jatropha curcus (jatropha) have received attention in the recent past as the sustainable oil sources for medicinal or bio‐diesel production .…”
Section: Introductionmentioning
confidence: 99%